Impactos da gestão ambiental da produção sucroenergética sob a perspectiva do desenvolvimento rural sustentável - Soares, Rodrigo Santolini (2017)
The Environmental management of the 20th century and beginning of the 21st century, with the ideals of environmental currents, starts to be a tendency of large contemporary companies. The environmental management by the perspective of sustainable rural development is one of the new strategic visions adopted by companies, this management passes a productive quality administration, sustainable production and environmentally controlled about its impacts. Sugar-energy sector organizations, producers of sugar, alcohol and energy, are inserted into productive processes and socio-environmental practices impacting to the environment. Consequently, they demand from an environmental legislation and the adoption of a contemporary environmental management system with a sustainable ecological vision. This research project identifies the organizations in the sugar-energy sector in the State of Mato Grosso do Sul, which they have this vision of sustainable rural development, and what practices of environmental management are benefiting them. The case study method was used to identify these qualitative objects, observing their productive processes and environmental prevention form. The results found indicate that the observed organization, with great economic potential and an environmental management model, turned to the impacts generated - social and environmental productive, complies with environmental legislation and it seeks sustainable rural development in the territory (or area of study). It concludes that an environmental management effectively brings a control of probable future expenses and a green marketing to the company’s brand and therefore, in a secondary way brings benefits to the increasingly demanding market. It’s important to emphasize that environmental management focused to the sector; it must to observe permanently to the integrated dimensions of sustainability as well as defense and equitable guarantee of environmental and social rights and the formation of environmental awareness.